“Whoever Does Not Thank People Has Not Thanked God”: Understanding the Relational Gratitude of Muslim Patients During the COVID-19 Pandemic - Naveed Baig (Religions)
As research on hospital experiences of religious minorities in the Global North increases, we still have scarce empirical knowledge about the role of religion and spirituality during crisis situations in hospitals. This study poses the following question: How do Muslim patients hospitalized with a severe disease express gratitude and how can it be interpreted? This was performed through a qualitative empirical method where twelve patients (eight males and four females) were interviewed at Danish hospitals during the COVID-19 pandemic. A thematic analytical approach was used to interpret and discuss the results. This study found that gratitude is channeled in different directions (God, family, and hospital staff). Patients express shukr, an Islamic theological concept, which means to thank, praise, and commend a benefactor—humans and God—in the Muslim worldview. Ultimately, shukr recognizes a blessing—especially its point of origin—and the response humans need to make for the act of Divine benefaction. Hence shukr for patients is not just a positive emotion but also a practice and a virtue with relational implications.